Choroidal thickness in normal Indian subjects using Swept source optical coherence tomography - Akhtar, Zeeshan; Rishi, Pukhraj; Srikanth, Ramasubramanian; Rishi, Ekta; Bhende, Muna; Raman, Rajiv (PloS one, 2018)
To determine choroidal thickness in healthy Indian subjects using Swept source optical coherence tomography (SS-OCT). In this prospective, observational, cross-sectional study; healthy Indian subjects (n = 230) with no history of ocular and/or systemic disorders were enrolled in the study. Choroidal thickness was measured for 230 eyes using SS-OCT. Subjects were divided into six age groups. Main outcome measures were subfoveal choroidal thickness (SFCT) and macular choroidal thickness (MCT) up to 3 mm at 500-micron interval from the fovea was measured in eight different quadrants. The mean SFCT was 307±79 μm and mean MCT was 285±75 μm. No difference in the choroidal thickness was found among genders. Mean SFCT of the different age groups was 327±68 μm (12-18 years), 364±70 μm (18.1-30 years), 321±78 μm (30.1-40 years), 304±79 μm (40.1-50 years), 283±69 μm (50.1-60 years) and 262±72μm (above 60 years; p <0.001; One way ANOVA). Mean macular choroidal thickness was 305±60 μm, 342±61 μm, 306±72 μm, 282±79 μm, 261±66 μm, 238±68μm respectively (p<0.001; one way ANOVA). A significant weak negative correlation was found between age with SFCT (r = -0.368, p<0.001) and MCT (r = -0.40, p<0.001). No significant correlation was found with refractive error, axial length and ocular perfusion pressure. This study showed that mean SFCT and MCT was 307±79μm and 285±75 μm, respectively, among healthy Indian subjects. Mean CT was found to decrease with age, although there was no difference in CT between genders.